COMMUNICATION IDENTITY WITHIN THE CASUAL FASHION ENTREPRENEUR COMMUNITY IN WEST JAVA AS A FORM OF PERSONAL BRANDING - Zane Rose Alfirda Kharomi Handoyo; Indra Novianto Adibayu Pamungkas (RADJA PUBLIKA, 2025)
This study aims to identify and analyze the communication identity formed within the casual fashion entrepreneur community in West Java and its contribution to building personal branding. A qualitative descriptive approach was employed, utilizing in-depth interviews with casual fashion entrepreneurs who are part of local creative communities. The primary theory used is the Communication Theory of Identity (CTI) by Michael Hecht, alongside the concept of personal branding from David Aaker, which encompasses five dimensions of individual brand character. The results show that the four layers of CTI (personal, enacted, relational, and communal) emerge simultaneously and intertwine in the entrepreneurs' communication processes. The findings also indicate that authenticity, consistency, emotional engagement, and community collaboration are the key strengths in forming a credible and impactful self-image. Through the exploration of each identity layer, this study confirms that communication is a central element in the formation of personal branding. Personal identity is manifested through a relaxed yet professional demeanor; enacted identity is evident in warm interactions and openness; relational identity is formed by maintaining personal character while adapting to social relationships; and communal identity is demonstrated through collaboration, product representation, and active participation in the community. These findings expand the understanding that personal identity is not only formed individually but also collectively through consistent communication practices within the business community. This study enriches the literature on communication identity in the context of the creative industry and provides a foundation for developing community-based personal branding strategies.